ANALISIS KEBIJAKAN NTMs AMERIKA SERIKAT TERHADAP PENOLAKAN EKSPOR TUNA INDONESIA KE PASAR AS PERIODE 2014-2021 - Valensius Primsa Ginting, (2023)
This thesis examines the Non-Tariff Measures (NTMs) policy implemented by the US towards Indonesian tuna products from 2014-2021. The application of NTMs by the US is relevant due to the significant number of rejections of Indonesian tuna products exported to the U.S. Out of a total of 1134 cases of rejected Indonesian fishery products, Indonesian tuna accounted for 795 cases, which is 70% of the total number of rejections of Indonesian fishery products to the U.S. during the 2014-2021 period. The high number of rejections of Indonesian tuna products has negatively impacted the image of Indonesian tuna products. This study utilizes a qualitative descriptive research method, specifically a case study, to analyze the NTMs policy applied by the United States towards Indonesian tuna products. The study draws on the concepts of International Trade, Non-Tariff Measures, and Classification of Non-Tariff Measures to analyze the data. The findings indicate that the high number of rejections of Indonesian tuna products is due to the inability of the Indonesian tuna industry to comply with the requirements imposed by the U.S. for exporting tuna products. Additionally, the study finds that the United States applies various types of NTMs towards Indonesian tuna products, including trade policies, tuna product standards, and certifications that burden the Indonesian tuna industry. Although consumer safety and environmental protection are the primary justifications provided by the United States for implementing NTMs, this study concludes that the application of NTMs by the US is also based on economic and political interests, specifically the protection of the domestic fishery industry in the US.